Synthesis, thermophysical properties and COSMO-RS study of DBU based protic ionic liquids - Losetty, V. (Academic Press, 2017)
In the present work, a new series of DBU based protic ionic liquids has been synthesized. The anions were generated from acetic acid, trifluoro acetic acid, methane sulfonic acid and trifluoro methanesulfonic acid. The obtained DBUAc, DBUTfa, DBUMsa and DBUTfmsa ionic liquids were characterized by 1H NMR and 13C NMR. The neat ILs were used to determine thermophysical properties namely density (ρ), viscosity (η) surface tension (γ) at various temperature ranges and atmospheric pressure (0.1 MPa). The experimental density and viscosity values were correlated using the linear and Vogel-Tammann-Fulcher (VTF) equations, respectively. Furthermore, thermal expansion coefficient (α) molar volume (Vm), thermodynamic surface properties and critical temperatures were estimated from experimental results. The lattice potential energy (UPOT) of the ILs was calculated to estimate the strength of ionic interactions between ions. In addition, the effect of water content on experimental results was measured and also estimated. The theoretical model namely COSMO-RS was used to study the ionic interactions in synthesized ionic liquids. Finally, the experimental and calculated results were discussed to understand the effect of temperature and moiety of ionic liquid on the thermophysical properties studied. © 2016